Empowerment of Socio-Economically Vulnerable Women (WRSE) through the Social Rehabilitation Program in South Kalimantan - Ghina Nur Rarin; Dewi Purboningsih (Pencerah, 2025)
The number of Women with Socioeconomic Vulnerability (WRSE) in South Kalimantan Province is still quite high, so an empowerment program was implemented by the Social Rehabilitation Center for the Disadvantaged in Social Barakat Cangkal Bacari (PRSTS BCB) aimed at increasing their independence. The purpose of this study was to analyze the WRSE empowerment process, as well as to determine the supporting and inhibiting factors in the empowerment. This study used a descriptive qualitative approach. Data were collected through observation, interviews conducted with 12 informants for 4 months, and documentation. Furthermore, the data were analyzed using the empowerment theory of The Three Principal Outcome-Focused Goals of Helping. The results showed that WRSE empowerment had gone well and met three empowerment indicators, namely: Life-enhancing outcomes for the client seen from socialization; selection and identification; assessment approach; and business capital assistance. Learning how to help oneself seen from skills guidance, entrepreneurship, and internship placement. Developing a prevention mentality seen from mental, social and religious guidance. The supporting factors for the program include 1) a mentality that does not give up easily, 2) professional instructors, 3) effective handling methods, 4) support from the family. Meanwhile, the inhibiting factors include: 1) limited budget, 2) limited human resources, 3) minimal information at the sub-district/village level, 4) lack of self-confidence, and 5) difficulty in accessing capital. Recommendations for further research are to explore the impact of empowerment on ex-clients.